2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.25591
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a Challenge-Inspired Undergraduate Experience

Abstract: undergraduate education through developing problem-based laboratories to enhance experimental design skills; developing a preliminary design course focused on problem identification and market space (based on an industry partner's protocol); and mentoring and guiding student teams through the senior design capstone course and a translational course following senior design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…12,17 Studies found that involving first-year students in engineering communities was key to early identification with engineering. For example, 'vertical mentoring', a process whereby more senior students provided 'laboratory tours and technique training, and social events', 18 was found to be effective for early identification with engineering, whilst collaboration with more senior students on laboratory projects was associated with commitment to an engineering career. 26,31 Conversely, students' inability to relate to the engineering profession and take on an emerging professional identity over time was exacerbated when there was a lack of interaction between novice and senior students.…”
Section: Results Of the Critical Review: How Laboratories Shape Engineering Identitiesmentioning
confidence: 99%
See 4 more Smart Citations
“…12,17 Studies found that involving first-year students in engineering communities was key to early identification with engineering. For example, 'vertical mentoring', a process whereby more senior students provided 'laboratory tours and technique training, and social events', 18 was found to be effective for early identification with engineering, whilst collaboration with more senior students on laboratory projects was associated with commitment to an engineering career. 26,31 Conversely, students' inability to relate to the engineering profession and take on an emerging professional identity over time was exacerbated when there was a lack of interaction between novice and senior students.…”
Section: Results Of the Critical Review: How Laboratories Shape Engineering Identitiesmentioning
confidence: 99%
“…1 Early identification with their profession is crucial for persistence amongst engineering students 17 ; students who do not develop a sense of belonging, identify with an engineering field or perceive themselves as engineers are more likely to abandon their studies. 4,14,18 Identification, or how students identify with engineering and are identified by others as an engineer, is 'formed out of a double-sided process of positioning ourselves and being positioned by others'. 19 Imagining future jobs in an engineering field is a key part of students' identification with engineering.…”
Section: Why Identity?mentioning
confidence: 99%
See 3 more Smart Citations